Factors that affect listening comprehension of Advanced Intensive English II students of the Bachelor of Arts in Modern Languages: Specialization in French and English and the Bachelor of Arts in English Language Teaching during semester I, 2018 - Hernández López, Silvia Guadalupe
The listening comprehension skill is a very important element for students while studying at the University of El Salvador. The objective of this research is to identify how some external factors such as access to internet, cable service, speakers‘ accents, environmental noise and length of recordings affect students‘ listening comprehension of Advanced Intensive English II students. Moreover, internal factors such as age, gender, lack of knowledge about the topic that is being presented and unknown vocabulary of the recording that is being heard will be analyzed to determine if they influence students‘ listening comprehension of Advanced Intensive English II of the BA in Modern Languages and the BA in English Teaching during semester I, 2018. To gather data, a questionnaire was distributed to four groups of students that represented 50% of the total population, the teachers in charge of each of group were interviewed, and a listening test was administered to the students. The data was analyzed using descriptive analysis and mixed method were applied in this research. The results reveal the participants‘ internal and external factors that affect their listening comprehension. Among the internal factors studied are the following: gender, age, students‘ lack of knowledge about the topic presented and unknown vocabulary of the recording that is being heard. Also, the participants‘ external factors such as, internet and cable service, speakers‘ accent, environmental noise and length of recordings were studied. The Foreign Languages Department of the University of El Salvador can use the results of this research to evaluate the current listening proficiency of the Advanced Intensive English II students enrolled in BA in Modern Languages and BA in English Language Teaching during semester I, 2018.